Early Bronze Age in Western Anatolia - Harrison, Laura K., 1985-; Bilgen, A. Nejat; Kapuci, Asuman, 1982- (State University of New York Press, 2021)
Examines the culture and chronology of increasingly complex urban societies in western Anatolia during the Early Bronze Age.
Keywords: Turkey -- Antiquities.; Excavations (Archaeology) -- Turkey.; Bronze age -- Turkey.; Material culture -- Turkey -- History.; Human settlements -- Turkey -- History.; Turkey -- History -- To 1453.; Archaeological dating -- Turkey.; Turquie -- Antiquités.; Asie Mineure -- Histoire.; SOCIAL SCIENCE / Archaeology.; Antiquities; Archaeological dating; Bronze age; Excavations (Archaeology); Human settlements; Material culture; Turkey; To 1453; History